The Good Cause Account of the Meaning of Life. Issue 4 (December 2013) - Smuts, Aaron
Abstract I defend the theory that one's life is meaningful to the extent that one promotes the good. Call this the good cause account (GCA) of the meaning of life. It holds that the good effects that count towards the meaning of one's life need not be intentional. Nor must one be aware of the effects. Nor does it matter whether the same good would have resulted if one had not existed. What matters is that one is causally responsible for the good. I argue that the best theory of the meaning of life should clearly distinguish between subjective fulfillment and objective meaningfulness. The GCA respects the distinction. And it is superior to its leading rivals in the recent literature, most notably those of Erik Wielenberg and Susan Wolf.